Samocenzura? Prehajanje med latinico in cirilico v osebni korespondenci pisateljic v obdobju slovenske moderne - Mlačnik, Primož (Slavia Centralis, 2024)
The paper is based on the author’s archival work and analysis of correspondence in the manuscript collection of the National and University Library (NUK), focusing on the correspondence of Slovenian modernist writers Marica Nadlišek Bartol, Zofka Kveder, Marica Strnad and Vida Jeraj, who cultivated epistolary friendships. The paper analyses their correspondence in the context of the New Censorship Theory to answer the question: Can alphabetical shifting from the Latin to the Cyrillic Script be perceived as a form of self-censorship? The analysis shows that female writers mostly used this alphabetic shift in their interpersonal letters when writing about the controversial topics of marriage, love, motherhood and sexuality. However, they were not consistent in this practice. The author considers this transition as a form of implicit, productive and inconsistent censorship, which, as a particular historical mode of writing, reflects broader socio-political changes.